Potential of Avitourism in Carey Island, Selangor - Syahmina Alwi, Amirah; Nor Atiqah; Hamdin, Muhammad Shafiq (Enhanced Knowledge in Sciences and Technology, 2024)
Avitourism or birdwatching is a growing segment of the nature-based tourism industry that provides several benefits to both travellers and destination towns. However, there is a lack of survey of the potential of avitourism conducted in Malaysia. Thus, this research was conducted to investigate the potential of avitourism in Carey Island, Selangor. This study aimed to provide an updated checklist of avian biodiversity and to investigate the potential of avitourism in Carey Island, Selangor, Malaysia. The study methods involved the collection of data from primary (direct observation techniques) and secondary sources (literature review). Out of 36 bird species found in the area, eight were shortlisted to be selected as flagship species based on eight criteria of a Good Nature Tourism Product including endemism, rarity, sighting reliability, morphological attractiveness, behavioural enticement, safety, linkage to local cultures, and ecological importance. The species are Common Kingfisher (Alcedo atthis), Chinese Pond Heron (Ardeola bacchus), Purple Heron (Ardea purpurea), Common Sandpiper (Actitis hypoleucos), Brown Shrike (Lanius cristatus), Cattle Egret (Bubulcus ibis), Crested Serpent-Eagle (Spilornis chee) and Blue-tailed bee-eater (Merops philippinus). This is next was further evaluated through the questionnaires that have been distributed to 63 respondents. From the result, Common Kingfisher (Alcedo atthis) was chosen as the flagship species. The study found that Carey Island, Selangor, has a high potential to develop avitourism, as it offers numerous benefits to travellers and destination towns.